Living Donor Liver Transplantation with Renoportal Anastomosis for a Patient with Congenital Absence of the Portal Vein - Hajime Uchida; Seisuke Sakamoto; Takanobu Shigeta; Ikumi Hamano; Hiroyuki Kanazawa; Akinari Fukuda; Chiaki Karaki; Atsuko Nakazawa; Mureo Kasahara (Case Reports in Surgery)
A congenital absence of the portal vein (CAPV) is a rare disorder that may lead to an intrapulmonary shunt. A 14-year-old male with CAPV underwent living donor liver transplantation with a left lobe graft from his father. The portal vein reconstruction was achieved with a renoportal anastomosis using an interpositional graft from the native collateral vein, because portal venous system directly drains to the left renal vein without constructing the confluence of superior mesenteric vein and splenic vein. The patient is doing well with a normal liver function and mild hypoxemia.